Current Status and Richness of Fishes in the Old Brahmaputra River of Bangladesh - Bari, Mohammad Rafiqul; Rahman, Habibur; Sultana, Sabina; Khandaker, Jebunnaher; Zim, Rukunuzzaman; Hasan, Mahmudul (Research in Agriculture Livestock and Fisheries, 2025)
The study, conducted from July 2019 to June 2020, aimed to assess fish richness and status in the Old Brahmaputra River, covering the stretch from Defla bridge (Islampur upazila) to Sharifpur (Jamalpur Sadar upazila). A total of 53 fish species was collected which belongs to 6 orders and 20 families. Among them catfish, loach, carp, barb, minnows, snakehead, clupeid, perch, mullet, eel corresponds to 16, 5, 6, 5, 5, 2, 2, 5, 2, 2 and 3 nominal fish species, respectively. Further, two additional fish species (Xenentodon cancila, Glossogobius giuris) was also documented. The Cyprinidae family recorded the highest number of species (21), while only one species was found in each of the Belonidae, Engraulidae, Clupeidae, Balitoridae, Erethistidae, Heteropneustidae, Siluridae, Gobiidae, Sciaenidae, Anabantidae, and Osphronemidae families. Of the 53 species; 13 was categorized as threatened, 2 species critically endangered [Bagarius bagarius, Sisor rhabdophorous], 7 species endangered [Botia lohachata, Barilius vagra, Crossocheilus latius, Clupisoma garua, Rita rita, Mastacembelus armatus] and 4 species vulnerable [Sparata aor, Wallago attu, Gudusia chapra, Sicamugil cascasia]. Exotic fish species (Cyprinous carpio var. communis) was recorded. The Simpson’s Diversity Index (SID= 0.9586) demonstrated high levels of diversity across these groups. This investigation not only highlights the species richness of Old Brahmaputra River but also aids in identifying key faunal elements of high conservation significance and assessing their potential risk of extinction. To restore the fish biodiversity of the Old Brahmaputra River proper conservation and management policy should be taken immediately. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 295-306